Procedure guideline for radioiodine test (version 2) - Dietlein, M.; Dressler, J.; Eschner, W.; Lassmann, M.; Leisner, B.; Reiners, C.; Schicha, H. (Nuklearmedizin - NuclearMedicine, 2003)
The version 2 of the procedure guideline for radioiodine test is an update of the guideline published in 1999. The following statements were added or modified: The procedure guideline discusses the pros and cons of a single measurement or of repeated measurements of the iodine-131 uptake and their optimal timing. Different formulas are described when one, two or three values of the radioiodine kinetic are available. The probe with a sodium iodide crystal, alternative or additionally the gamma-camera using the ROI-technique are instrumentations for the measurement of iodine-131 uptake. A possible source of error is an inappropriate measurement (sonography) of the target volume. The patients’ preparation includes the withdrawal of antithyroid drugs 2-3 days before radioiodine administration. The patient has to avoid iodine-containing medication and the possibility of additives of iodide in vitamin- or electrolyte-supplementation has to be considered.
Keywords: Toxic goitre; Graves’ disease; hyperthyroidism; radioiodine test; procedure guideline